Morphological and anatomical study of Russell's lisianthus herb - Olefirenko , Anna; Kyslychenko, Viktoriya (Annals of Mechnikov's Institute, 2023)
Introduction. Ornamental plants have long attracted the researchers’ attention as a promising source of remedies with a sufficient raw material base. Such plants include Russell's lisianthus (Lisianthus russellianus Hook.) or large-flowered eustoma (Eustoma grandiflorum (Raf.) Shinners) of the Gentianaceae family (Gentianaceae Juss.), which began to be widely cultivated in many countries as an ornamental plant in the 70-s of the 20th century. Since Russell's lisianthus spread Eurasia territory relatively recently, this plant chemical composition has not been sufficiently studied. It is known to contain xanthones, secoiridoids, and flavonoids (derivatives of pelargonidin, delphinidin, kaempferol, quercetin, and isorhamnetin). In traditional medicine, Russell's lisianthus is used to treat constipation, anorexia, fever, tuberculosis, and nervous exhaustion. Most of Russell's lisianthus studies are devoted to its agricultural techniques. In the available sources of domestic and foreign scientific literature, there is almost no information on the morphological and anatomical study of Russell's lisianthus herb. The aim of the work was to determine of the diagnostic morphological and anatomical features of the herb (stems, leaves and flowers) of Russell's lisianthus of the Borealis Apricot species. Materials and methods. Lisianthus Russell herb of the Borealis Apricot species harvested in August 2023 in the Kharkiv region (Ukraine) was used for the study. Morphological research was carried out on fresh and dried plant samples. The external features were determined visually and with a magnifying glass (x10). The plant raw material was fixed in a mixture of ethanol - glycerin - water (1:1:1) for anatomical research. Diagnostic microscopic examination was carried out according to the methodology of the State Pharmacopoeia of Ukraine 2.0, volume 1, general article 2.8.23 "Microscopic examination of medicinal plant raw material". The anatomical structure of the plant raw material was studied with the help of light microscopes "Lomo Mikmed-1" and "Granum" with a digital camera "Digital camera for microscope DCM 300". Results. A morphological and anatomical study of the stems, leaves and flowers of Russell's lisianthus of the Borealis Apricot species, grown in Ukraine, was carried out. The identified morphological features include: the stem of Russell's lisianthus is herbaceous, bare, upright, cylindrical in shape, and rounded in cross-section. The leaves are sessile, stem-wrapped, simple, entire, ovate or linear-lanceolate, with a pointed tip. The convex main vein is clearly visible from the lower side. The type of venation is arcuate. The flowers are bisexual, regular, actinomorphic, with a double perianth, on long thin peduncles, with five green sepals fused only at the base. The corolla in the buds is twisted. Petals of an oval, almost rounded shape, joined only at the base. Defined anatomical features include: stem epidermal cells are rectangular, with stomata of the paracytic type, surrounded by 3-4 peri-stomate cells. The leaf epidermis on both sides consists of densely convoluted cells with evenly thickened walls, which are smaller in size on the lower side. The leaf is amphistomatic, stomata of the anomocytic type. The cells of the upper and lower epidermis of the flower petal of Russell's lisianthus are elongated. Vents are very rare. Sepal epidermal cells of prosenchymal form. Conclusions. The morphological and anatomical structure of Russell's lisianthus herb, grown in Ukraine, was studied for the first time. Characteristic anatomical features are the nature of the epidermis cells of the leaf, stem, petal and sepal; stomata of the anomocytic type, located on the on both sides of the leaf epidermis, stem and sepal; amphistomatic leaf structure. For the first time the main macroscopic and microscopic features of whole, crushed and powdered plant raw material were determined. This fact will allow the identification of the studied plant and will be used in the development of the "External features" and "Microscopic features" sections of the "Russell's lisianthus herb" project of quality control methods. Keywords: Russell's lisianthus (Lisianthus russellianus Hook.), herb, morphology, anatomy